Orientalis dan Kajian Islam di Indonesia: Studi tentang Model Islam Politik - Asyari, Suaidi (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2005)
This study discusses variations of models or approaches that have been used by orientalists in studying the relationships between Islam and politics in Indonesia. The writer has used socio-historical approach in order to categorize the models or approaches. Generalization that has been employed by orientalists on Islam and politics in Indonesia, both in its relation to the state and other groups, can be simplified into deconfessionalization, domestication, schismatic and variant, trichotomy, and cultural Islam. It can be concluded, from this study, that analysis that has been used by orientalists has not been always negative. Therefore, their works will always be relevant and useful as references in studying relations between Islam and politics in lndonesia.